2007
DOI: 10.1063/1.2777147
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the work function of poly(3,4-ethylenedioxythiophene) doped with poly(4-styrenesulfonate) by ultraviolet irradiation

Abstract: The effects of ultraviolet (UV) irradiation on the work function of poly(3,4-ethylenedioxythiophene) doped with poly(4-styrenesulfonate) (PEDOT:PSS) have been investigated in this study. Spectroscopic methods [x-ray photoelectron spectroscopy and Raman spectroscopy (532nm excitation)] and electrical conductivity measurements were used to characterize the electrical conducting polymer PEDOT:PSS prepared by UV irradiation. The authors found that UV irradiation could lead to an increase in the work function and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(46 citation statements)
references
References 24 publications
1
45
0
Order By: Relevance
“…function enhancement is critical to device performance. Lin et al [ 22 ] and Moujoud et al [ 7 ] found that UV irradiation could lead to an enhancement in conductivity and the work function of PEDOT:PSS. In order to study the mechanism of conductivity enhancement in PEDOT:PSS fi lms through UV-light treatment, Moujoud et al [ 7 ] employed X-ray photoelectron spectroscopy (XPS) and ultraviolet photoelectron spectroscopy (UPS) to investigate the electronic and structure changes in PEDOT:PSS fi lms.…”
Section: Introductionmentioning
confidence: 99%
“…function enhancement is critical to device performance. Lin et al [ 22 ] and Moujoud et al [ 7 ] found that UV irradiation could lead to an enhancement in conductivity and the work function of PEDOT:PSS. In order to study the mechanism of conductivity enhancement in PEDOT:PSS fi lms through UV-light treatment, Moujoud et al [ 7 ] employed X-ray photoelectron spectroscopy (XPS) and ultraviolet photoelectron spectroscopy (UPS) to investigate the electronic and structure changes in PEDOT:PSS fi lms.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests negligible change in the trapped charges in the UV-treated PEDOT:PSS film. Based on the above result, we suggest that UV treatment may lead to a decreased number of charge-trapping-related defects, resulting in increased conductivity of PEDOT:PSS (that is, a reduction in R s ) [11,20]. On the other hand, the shape of the normalized C-V curve shown in Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Ko et al [2] suggested that doping of PEDOT:PSS mainly affects R s only in the vertical direction. Recently, a method for enhancing the conductivity of PEDOT:PSS based on ultraviolet (UV) treatment was reported [11,12]. Benor et al [13] reported the use of UV-ozone exposure of PEDOT:PSS for improving the efficiency of OLEDs.…”
Section: Introductionmentioning
confidence: 98%
“…Fortunately, the work function of PEDOT:PSS can be increased via treatment with UV-ozone or by mixing or covering with Nafion ® . [14][15][16][17][18] The changes in work function are reported to be 0.13 to 0.25 eV for UV-ozone treated films, [14][15][16] up to 0.65 eV for the films with Nafion ® . 17,18 Here we present poly͓3,6-di͑4Ј-ethyloctyl͒thieno ͓3,2-b͔ thiophene-2,5-diyl-2,1,3-benzothiadiazole-4,7-diyl͔ ͑PTTBT͒ ͑Fig.…”
mentioning
confidence: 99%